2023
DOI: 10.4300/jgme-d-22-00229.1
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Footprint and Cost of Virtual Residency Interviews

Abstract: Background The shift from in-person to virtual residency interviews may impact greenhouse gas emissions (GHGE) and costs but the direction and amount of this change is not yet clear. Objective To estimate GHGE and financial impacts of virtual interviews among applicants and programs. Methods In 2020-2021 we sent a postinterview survey to 1429 applicants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…37 During the COVID-19 pandemic, many US fellowship programs transitioned to virtual interviews, resulting in a median estimated reduction of 0.47 metric tons of CO 2 emissions per applicant per interview, 98% of which can be attributed to decreased air travel. 38 Moreover, virtual interviews offered time and cost savings for both applicants and programs, with approximate savings of $490 per applicant per interview and program savings ranging from $7615 to $33,670. 38 However, it is important to consider the downsides of virtual interviews, such as a lack of personal interaction and familiarity with the institution and the neighborhood.…”
Section: Carbon Footprint Mitigation Strategies In Fellowship Recruit...mentioning
confidence: 99%
See 1 more Smart Citation
“…37 During the COVID-19 pandemic, many US fellowship programs transitioned to virtual interviews, resulting in a median estimated reduction of 0.47 metric tons of CO 2 emissions per applicant per interview, 98% of which can be attributed to decreased air travel. 38 Moreover, virtual interviews offered time and cost savings for both applicants and programs, with approximate savings of $490 per applicant per interview and program savings ranging from $7615 to $33,670. 38 However, it is important to consider the downsides of virtual interviews, such as a lack of personal interaction and familiarity with the institution and the neighborhood.…”
Section: Carbon Footprint Mitigation Strategies In Fellowship Recruit...mentioning
confidence: 99%
“…38 Moreover, virtual interviews offered time and cost savings for both applicants and programs, with approximate savings of $490 per applicant per interview and program savings ranging from $7615 to $33,670. 38 However, it is important to consider the downsides of virtual interviews, such as a lack of personal interaction and familiarity with the institution and the neighborhood. Virtual interviews may also limit the program director's ability to gauge an applicant's interpersonal and behavioral skills.…”
Section: Carbon Footprint Mitigation Strategies In Fellowship Recruit...mentioning
confidence: 99%
“…This required programs to adapt their interview process without precedent or guidance from the literature. Since then, studies have demonstrated the advantages of VIs, including financial savings for applicants and programs, reduced time away from clinical responsibilities, reduced carbon emissions, time efficiency, less pressure during interviews, the ability for applicants to interview at a greater number of programs and a more equitable interview process [1][2][3][4][5][6][7]. However, studies show that the lack of in-person connection makes it difficult for applicants to assess a program's culture, as the perception of culture is influenced by direct and personal interactions [1,3,6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Programs and applicants alike have recognized the cost savings from virtual processes, along with a reduction in the carbon footprint produced by past recruitment cycles. 12 These practices reflect the broader movement in graduate medical education toward improving equity by reducing costs and time burden for applicants, and better diversifying the future physician workforce.…”
mentioning
confidence: 99%
“…The increasing debt burden of graduating medical students includes thousands of dollars for applications and travel to in-person interviews, placing those with financial constraints at a significant disadvantage. Programs and applicants alike have recognized the cost savings from virtual processes, along with a reduction in the carbon footprint produced by past recruitment cycles 12 . These practices reflect the broader movement in graduate medical education toward improving equity by reducing costs and time burden for applicants, and better diversifying the future physician workforce.…”
mentioning
confidence: 99%